Navigating the Waters: Lessons Learned from Junior PETE Faculty Members. (2nd January 2020) - DiGiacinto, Kacey; Culp, Brian; Hersman, Bethany; James-Hassan, Martha; Johnson, Britton
ABSTRACT: This article will highlight aspects of the key elements that will benefit junior PETE faculty members who are seeking to advance their careers. This article will highlight tips for junior faculty members for succeeding at: building relationships across campus, creating a mentor and mentee relationship, progressing towards tenure and promotion, and attaining work-life balance. Finally, the article will reflect on the promotion and tenure process and discuss how to help junior faculty members succeed.